Nanotubes mediate niche-stem cell signaling in the Drosophila testis - Inaba, Mayu (Nature, 2015)
Stem cell niches provide resident stem cells with signals that specify their identity. Niche signals act over a short-range such that only stem cells but not their differentiating progeny receive the self-renewing signals(1). However, the cellular mechanisms that limit niche signaling to stem cells remain poorly understood. Here we show that the Drosophila male germline stem cells (GSCs) form previously unrecognized structures, microtubule-based (MT)-nanotubes, which extend into the hub, a major niche component. MT-nanotubes are observed specifically within GSC populations, and require IFT (intraflagellar transport) proteins for their formation. The BMP receptor Tkv localizes to MT-nanotubes. Perturbation of MT-nanotubes compromises activation of Dpp signaling within GSCs, leading to GSC loss. Moreover, Dpp ligand and Tkv receptor interaction is necessary and sufficient for MT-nanotube formation. We propose that MT-nanotubes provide a novel mechanism for selective receptor-ligand interaction, contributing to the short-range nature of niche-stem cell signaling.